AUTOMATED GEOMETRIC SIMULATION OF AIRCRAFT CIRCUITS OF PARABOLO-ELLIPTIC AIRCRAFT AIRCRAFT ENGINES - Ситниченко, В. В. (Proceedings of National Aviation University (archive), 2021)
The issue of automation of geometric modeling of parabolo-elliptical contours of characteristic cross-sections of air intakes of aircraft gas turbine engines under given conditions (parameters) is considered.